Mosque Institutions in Malaysia: what is the concept of the lyrics? - Mohd Aderi Che Noh; Ismail Jaafar (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
This article comprises discussions related to the concept of the Mosque in Malaysia, as far as conforming to the idea of rahmatan lilalamin, which is the primary basis of the Prophet Muhammad SAW. Contrary to the concept of rahmatan lilalamin then came Rahmah Mosque, which is concerned with the unification and peace of the universal ummah. This also repels a narrow understanding of the function of the mosque. In this paper, the author discusses the challenge of establishing a mosque institution that conforms to the concept of rahmatan lilalamin to expose readers to fend off all the extreme views of mosque functions. At the end of the writing, it is reiterated that the role of the mosque should be in line with the concept of lilalalmin's grace. This is based on the management, supervision, infrastructure facilities and mosque environment that can create the love of one's fellow Muslims and have a different society.Artikel ini terdiri dari diskusi yang berkaitan dengan konsep Masjid di Malaysia, sejauh sesuai dengan gagasan rahlatan lilalamin, yang merupakan dasar utama Nabi Muhammad SAW. Bertentangan dengan konsep rahmatan lilalamin kemudian muncul Masjid Rahmah, yang berkaitan dengan penyatuan dan kedamaian ummah universal. Ini juga mengusir pemahaman sempit tentang fungsi masjid. Dalam makalah ini, penulis membahas tantangan mendirikan lembaga masjid yang sesuai dengan konsep rahmatan lilalamin untuk mengekspos pembaca untuk menangkis semua pandangan ekstrem fungsi masjid. Di akhir tulisan, ditegaskan kembali bahwa peran masjid harus sejalan dengan konsep rahmat lilalalmin. Ini didasarkan pada manajemen, pengawasan, fasilitas infrastruktur dan lingkungan masjid yang dapat menciptakan kecintaan sesama Muslim dan memiliki masyarakat yang berbeda.